(untitled) (Journal of Laboratory Animal Science, 2024)
Animal models of hypertension are crucial for studying the pathophysiology of diseases and developing new treatments. This study introduces a reproducible technique for inducing surgical renovascular hypertension in rats using a smaller renal artery clip. The surgical groups were compared to the control group and standard drug group to assess the effectiveness of the surgical model and its stability for 21 days. The results revealed a progressive increase in systolic and diastolic blood pressure in the surgical group. Moreover, the heart rate and body weight in the renal hypertension group demonstrated a sustained elevation at the end of 21 days. These findings confirm the efficacy of this surgical model in inducing hypertension. This surgical animal model is helpful for studying physiological parameters for investigating potential therapeutic interventions against hypertensi